Directional dependence of critical axial strain in X65 pipeline steel subject to combined internal pressure and bending loading. (April 2022) - Sakonder, C.; Xue, L.; Paredes, M.; Savioli, R.; Sarzosa, D.F.B.
Abstract: In this exploratory study, a X65 seam weld pipeline steel is investigated by considering the effect of anisotropy on plasticity and fracture responses of biaxially (combined bending and internal hydrostatic pressure) loaded pipes having different crack lengths, diameter sizes and internal pressure levels. The results indicate that directional dependency is strong for pipes with relatively large diameters, deep cracks and loaded at high internal pressure. However, critical strain seems to be slightly influenced by anisotropy when the pipe diameter-to-thickness ratio decreases. That is, smaller pipes are quite insensitive to its effect irrespective of crack depth, crack length and internal pressure level.